Evolution of 3 generations of school design / Afizi Sahar - Sahar, Afizi (2005)
The main purpose of this dissertation is to study, identify and understand the potential of school design physically, which is essential in boosting learning and teaching experience of student and teachers. In our learning curve from standard 1 to form 5 or form 6, we lack of attention on school design which was once a part of our life, before we hop into university or working market. Although schools for most of us at that time is just for learning, playing and make friends, but we lack of the significant knowledge of why is some school have a very unique design and most of the schools is just linear meaning that the design is just blocks and blocks. In this study, the author is therefore involved in researching the gradual changes in school design and the essence of evolution. Furthermore, how a simplest thing such as school design can have an effect on the student in their immense learning and development.